Analysis of Oil Spill and Sea Ice Measurements Using Full-Polarimetric and Hybrid-Polarity Synthetic Aperture Radar data - Espeseth, Martine (IEEE Transactions on Geoscience and Remote Sensing, 2019)
Synthetic Aperture Radar (SAR) data has been used for decades to detect oil slicks and monitoring sea ice. With increased oil and gas exploration in the Arctic follows higher risk for oil spills. Knowledge of the sea ice and oil spills is important for making clever and efficient decisions in a hectic and non-hectic operational situation. The potential and limitations of the hybrid-polarity (HP) SAR mode for oil spill and sea ice applications are evaluated in this thesis, and results show that the HP mode is almost as good as the full-polarimetric (FP) SAR mode. This thesis also recommends FP and HP features suitable for oil slick detection. These are identified to have a strong connection to oil damping of the small-scale ocean surface roughness in two-scale Bragg models. Separability of various Arctic sea ice is evaluated, and the results indicate a similar separability performance using real- and simulated HP data. The backscattered signal from oil slicks might be contaminated by various system noise sources, especially for spaceborne instruments. This will limit the ability to use the data for any scattering analysis or information extraction of physical oil properties. A set of well known polarimetric features are shown to be highly influenced by system noise, both additive and multiplicative. The reasons for what has often been assumed a different scattering mechanism within oil slicks, frequently termed non-Bragg in the literature, is concluded to mainly be a result of system noise. This thesis also explores methods that provide complementary information products that could be valuable in the oil spill recovery process. The methodologies are aimed at creating maps that combine several SAR images to make products that quantify and visually depict the temporal evolution of the slick in an easily understandable representation.